High entropy nanomaterials for energy storage and catalysis applications - Modupeola, Dada; Popoola, Patricia (Frontiers in Energy Research, 2023)
In the past decade, high entropy alloys have been a research field of interest largely attributed to the enormous possibilities in alloy compositions, solid solution microstructures, and enhanced properties. The progress accomplished so far in the innovative growth and development of the mechanical, nanomechanical, chemical, electrochemical properties for energy storage systems using high entropy alloys on the nanoscale has limited reports in the literature. Mastering the synthesis of high entropy alloys is the deciding factor, if not the holy grail, when interested in a new material. For nanoparticles, in particular, this is true. Hence, the study on the production of high entropy alloy nanoparticles (HE-NPs) and the impact of synthesis on the structure of the resulting nanomaterial is valid for newly emerging components like HEA-NPs and the linkages between synthesis, structure, and property are essential for creating HEA-NP-based applications for energy storage applications, requiring the creation of a fundamental protocol to enable their mass manufacture and efficiency in service. In this study, we have presented a straightforward review of high entropy alloys, recent advances in high entropy nanoparticles and their various syntheses for energy and catalysis applications.